Widening access to isotretinoin in primary care: an evaluation of New Zealand national dispensing data for isotretinoin for acne, 2008–2023 - Bruce Arroll; Diarmuid Quinlan; Peter Moodie; Rachel Petronella Roskvist; Jason Arnold (BMJ Open)
Objectives To identify what changes in the prescribing of isotretinoin have occurred since funded prescriber access was widened in 2009 from ‘dermatologist only’ prescribing to include ‘general practitioners (GPs) and nurse practitioners working within their scope of practice’.Design Evaluation of isotretinoin dispensing data from 2008 to 2023 using the national annual prescribing data obtained from the New Zealand Pharmaceutical National Collection database.Setting All New Zealand citizens prescribed and dispensed funded isotretinoin for acne from 2008 to 2023 were included.Main outcome measures The prescribing data were analysed to identify the total number of prescriptions per year by prescribing clinician type, patient ethnicity and deprivation levels.Results In 2008, nearly 100% (26 897) of dispensed prescriptions were written by a dermatologist, while in 2023, 79% (39 432) were written by primary care clinicians. Annual isotretinoin prescriptions increased by 87%, from 26 897 (2008) to 50 613 (2023). Prescriptions for Māori increased from 1750 in 2008 to 4374 in 2023, with similar increases for other ethnic minorities.Conclusion Expanding the prescriber cohort has resulted in a substantial increase in prescriptions, with primary care now issuing the majority of isotretinoin prescriptions. These data demonstrate that the GP workforce can absorb and manage the additional acne workload from the increasing population. Enhanced access for patients suggests an unmet need. An absolute number of prescriptions have risen faster for Māori and Asian patients than for Europeans. Pacific people were generally lower than Europeans. This suggests the longstanding ethnic disparity in access to isotretinoin is partially reduced.Many countries have restrictions on patient access to isotretinoin, similar to New Zealand in 2008. This is the first study demonstrating that, given appropriate postgraduate education and support, the isotretinoin risk–benefit profile may be enhanced to safely deliver high-quality, timely, equitable patient access to isotretinoin in primary care.